GIS an introduction to mapping technologies - McHaffie, Patrick; Hwang, Sungsoon; Follett, Cassie (Boca Raton, FL CRC Press, 2023)
This second edition of "GIS" is thoroughly rewritten and adds two new chapters to respond to today's students' demand for critical engagement with technologies that address relevant issues across several disciplines, and prepares them for higher-level work in geotechnologies. Chapters are arranged to build competence in fundamental skills, explore applications of higher-level managerial and analytical functions that are called upon in public, non-profit, and private sector milieu, and propose a detailed template for organizing, executing, and completing a GIS project successfully. This interests all users from beginners to experienced professionals"--
First edition published by CRC Press 2018"--Title page verso.
Includes index.
Keywords: Geographic information systems; Geotechnical engineering; Information storage and retrieval systems -- Geography